Anti-Apoptotic and Pro-Apoptotic Bcl-2 Family Proteins in Peri-Implant Diseases - Yilmaz Dogukan; Gürsoy Mervi; Gürsoy Ulvi Kahraman (WILEY, 2025)
Objectives
Intrinsic apoptosis, which is regulated by Bcl-2 family proteins, has an important role in chronic inflammatory diseases. The aim of the study was to identify the tissue levels and ratios of anti- and pro-apoptotic Bcl-2 family proteins in peri-implant diseases.
Materials and Methods
Twenty-three individuals with peri-implant mucositis, 25 individuals with peri-implantitis, and 24 controls were included. The following clinical parameters were recorded: keratinized mucosa width, modified bleeding index, probing depth, modified plaque index, modified gingival index, and keratinized tissue thickness. Marginal alveolar bone assessments were performed by a software program. Granulation tissues were collected during treatments of peri-implant diseases. The control tissue samples were collected during the second stage of implant surgery. The tissue levels of Bcl-2 family pro-apoptotic (Bak, Bax, active caspase-3) and anti-apoptotic (Bcl-2, Bcl-xL, Mcl-1) proteins were determined by multiplex immunoassay method.
Results
The pro-apoptotic proteins; Bak, Bax and anti-apoptotic proteins Bcl-2, Bcl-xL, Mcl-1 were detected significantly higher in controls compared with patients with peri-implant mucositis and peri-implantitis (p < .001), respectively. The higher active caspase-3 levels were also detected in controls in comparison with peri-implant mucositis (p = .018) and peri-implantitis (p = .005). Anti-apoptotic: pro-apoptotic protein ratios (Bcl-2:Bax, p < .001; Bcl-2:Bak, p = .01; Bcl-xL: Bax, p = .006, Bcl-xL:Bak, p = .011; Mcl-1:Bak, p < .001) were significantly increased in diseased groups. A positive correlation was demonstrated between clinical variables and anti-apoptotic: pro-apoptotic ratios.
Conclusion
Our findings indicate dysregulation of the Bcl-2 family proteins in peri-implant diseases. This unregulated response may disturb the homeostasis of peri-implant tissue.